2001
DOI: 10.1113/jphysiol.2001.012836
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P2X2 and P2X3 receptor subunits in rat carotid body afferent neurones: role in chemosensory signalling

Abstract: 1. Hypoxic chemotransmission in the rat carotid body (CB) is mediated in part by ATP acting on suramin-sensitive P2X purinoceptors. Here, we use RT-PCR, cloning and sequencing techniques to show P2X2 and P2X3 receptor expression in petrosal neurones, some of which develop functional chemosensory units with CB receptor clusters in co-culture. 2. Single-cell RT-PCR revealed that hypoxia-responsive neurones, identified electrophysiologically in co-culture, expressed both P2X2 and P2X3 mRNA. 3. Isohydric hypercapn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(126 citation statements)
references
References 0 publications
9
108
1
4
Order By: Relevance
“…Carotid chemotransduction is critically dependent upon ATP and (specifically) P2X2 receptor activation (Gourine et al, 2005; Prasad et al, 2001; Rong et al, 2001; Zhang et al, 2000). PPADS attenuated the short-term hypoxic phrenic response by >80%, confirming ATP’s critical role in peripheral chemoreflexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carotid chemotransduction is critically dependent upon ATP and (specifically) P2X2 receptor activation (Gourine et al, 2005; Prasad et al, 2001; Rong et al, 2001; Zhang et al, 2000). PPADS attenuated the short-term hypoxic phrenic response by >80%, confirming ATP’s critical role in peripheral chemoreflexes.…”
Section: Discussionmentioning
confidence: 99%
“…ATP, acting via ionotropic P2X 2 receptors, is a critical neurotransmitter in peripheral chemoreceptor function (Prasad et al, 2001; Rong et al, 2001; Zhang et al, 2000). As such, ATP receptor antagonists that do not cross the blood–brain barrier inhibit carotid chemoafferent activity during hypoxia, while maintaining chemoafferent synaptic connections in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…During hypercapnia, the increase in ATP release occurred 19.5 ± 4.8 ms before the induction of breathing. Based on above evidence, they hypothesized that ATP-mediated afferent transduction may also occur in the central chemoreception (Spyer et al, 2004; Gourine et al, 2005), as is described in peripheral chemoreception (Prasad et al, 2001; Zapata, 2007; Piskuric and Nurse, 2013). …”
Section: Cx- and Panx Channels In Central Chemoreceptionmentioning
confidence: 98%
“…In the present study, we examined the N current using conventional whole-cell patch-clamp configuration. We demonstrated that a CTX-sensitive N current exists in ovine somatotropes, but this current accounts for less than 10% of the total Ca 2+ current, a much smaller proportion than it accounts for in neurons [45]. The T current has been demonstrated in ovine somatotropes and gonadotropes, but is negligible in the GH3/B6 cell line [22, 46, 47].…”
Section: Discussionmentioning
confidence: 99%